The Spirit of Bali Traditional Law in Development National Law in the Age of Globalization - I Putu Gelgel (Warmadewa Press, 2022)
The fact that we see that the development of law (legal substance, legal structure and legal culture) in our country is still running hobbled behind the dynamics of social and cultural life of society. This fact is one of the sources of the chaotic face of law in Indonesia. By looking at these conditions, the sprit of Balinese Customary Law in the development of National Law really needs to be initiated, studied, and developed. The law should be built in line with the socio-cultural structure of our own nation, but still be able to accommodate the dynamics of its socio-cultural life in this era of openness. Through that Balinese Customary Law will be able to contribute to the development of National Law.